Evolutionary clinical characteristics of single application of calcium alginate in second-degree burns - Carranza-Castillo, Julio Enrique (2024)
Objetive: To determine the evolutionary clinical characteristics of the single application of calcium alginate in the treatment of second-degree burns. Methods: Observational, descriptive, quantitative study, where were included 64 patients with second degree A and B burns who attended the Fátima Clinic in Trujillo, Farmédica Clinic, and the Víctor Lazarte Echegaray Hospital (EsSALUD) were included, and were evaluated. 83 burn injuries were evaluated, pain, infection, acceptance and additional healing will be considered in each burn. Results: The burns evaluated were 44 second degree A and 39 second degree B burns, likewise, of the total patients, 60.9% were female, and 39.1% were male; the prevalent age was 30-59 years (32.8%) and by 1 to 11 years (29.7%). When applying calcium alginate, the average healing time for all patients was 16.3 days, there was mild pain in more than 97% of the cases, no case presented infection, rejection of the alginate was reported in each group . which represents 2.4%, and 2.3% required additional healing in second degree A burns and 17.9% in second degree B burns. Conclusion: Calcium alginate is an alternative for the treatment of second degree burns. , the average healing time was 16 days, no infection, no rejection of the dressing, the pain was mild in the majority of patients.